Analysis of Leadership Style and Characteristics On Teacher Performance as an Intervening Variable Elementary School in Bababalan District, Langkat Regency - Wenny Ramadani; Desi Astuti; Hernawaty Hernawaty (Utan Kayu Publishing, 2026)
Improving the quality of basic education largely depends on teacher performance quality, which is influenced by various determinant factors. This study aims to analyze the role of professional competence as an intervening variable in the relationship between teacher characteristics and teacher performance in elementary schools in Babalan District, Langkat Regency. The research employed a quantitative approach involving 66 teachers from five elementary schools selected as case studies. Data were collected through Google Form-based online questionnaires with a 1-4 Likert scale and analyzed using path analysis with the assistance of SPSS. The results showed that teacher competence significantly affects teacher performance (B = 0.530; p 0.01), while teacher characteristics proved significant in forming professional competence (B = 0.529; p 0.01). Interestingly, the findings revealed that the principal's leadership style showed no significant effect either directly on performance or indirectly through competence. The Sobel test confirmed that competence significantly mediates the effect of teacher characteristics on performance (Z = 2.83), but does not mediate the relationship between leadership style and performance. The implications of this study recommend focusing development on specific and applicable teacher competency enhancement, as well as optimizing positive teacher characteristics that have been proven to be an important foundation in improving educational performance.